Question #35046

2 Answers
Feb 15, 2018

x=-6.9

Explanation:

Divide both sides by 3

-6.9=(3(x+4.6))

-6.9/3=(3(x+4.6))/3

-2.3=x+4.6

Subtract both sides by 4.6

-2.3-4.6=x+4.6-4.6

-6.9=x+0

-6.9=x

Alternatively, begin by distributing 3 each term in x+4.6

-6.9=3(x+4.6)

-6.9=3x+13.8

Subtract 13.8 from both sides:

-6.9-13.8=3x+13.8-13.8

-20.7=3x+0

-20.7=3x

Divide both sides by 3:

-20.7/3=3/3x

-6.9=x

Feb 15, 2018

the answer is x=-6.9

Explanation:

first distribute 3 to the inside equation. then subtract 13.8 with -6.9 then divide by 3